2000
DOI: 10.1210/en.141.9.3471
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Estrogens Directly Alter Androgen-Regulated Prostate Development

Abstract: Neonatal exposure to high doses of estrogen results in permanent suppression of prostate growth and reduced sensitivity to androgens in adulthood. It is unclear whether alterations in prostate growth are due to a direct effect of estrogens on the gland or are the result of hypothalamic-pituitary-gonadal axis suppression and a subsequent reduction in androgen levels. Therefore, the aim of this study was to determine whether estrogens have a direct effect on the prostate using a defined method of culturing neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…In the dorsal and lateral lobes, not only is growth reduced but severe branching deficiencies exist such that elongating ducts fail to develop secondary and tertiary branch points and complex morphology (50). While reduced growth is in part a function of reduced circulating T levels following neonatal estrogen exposure (48), organ culture studies also demonstrated a direct effect of estrogens in growth retardation as well as altering prostate differentiation (51,52).…”
Section: Rat Model Of Developmental Estrogenizationmentioning
confidence: 99%
“…In the dorsal and lateral lobes, not only is growth reduced but severe branching deficiencies exist such that elongating ducts fail to develop secondary and tertiary branch points and complex morphology (50). While reduced growth is in part a function of reduced circulating T levels following neonatal estrogen exposure (48), organ culture studies also demonstrated a direct effect of estrogens in growth retardation as well as altering prostate differentiation (51,52).…”
Section: Rat Model Of Developmental Estrogenizationmentioning
confidence: 99%
“…As there is increasing evidence that the prostate is a target for direct oestrogenic activity (Jarred et al 2000, Putz et al 2001, it is important to determine whether or not aromatase is expressed locally and to identify any changes that may occur with prostate disease. To date, aromatase expression in the prostate is contentious because the detection of enzymic activity or gene expression is equivocal; numerous reports have detected or failed to detect aromatase in prostatic tissue (Smith et al 1982, Kaburagi et al 1987, Stone et al 1987, Brodie et al 1989, Matzkin & Soloway 1992, Tsugaya et al 1996, Hiramatsu et al 1997, Negri-Cesi et al 1998, 1999.…”
Section: Aromatase In Prostatementioning
confidence: 99%
“…18,21,43,44 Previous studies from conventional ER KO mice revealed that ERa, not ERb, is the critical receptor to mediate the estrogens response in those processes. 7,8,19,21 To investigate the in vivo roles of ERb in mouse prostate development, the neo-ERbKO mouse model was applied. The neo-ERbKO male mice from Chapel Hill revealed a hyperplastic prostate, 13 while the same transgenic mice housed at Karolinska Institute presented with prostatic intraepithelial neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In contrast, higher doses of estrogens permanently suppress the neonatal rat or mouse prostate growth and prostatic branching morphogenesis by reducing testosterone (T) production, suppressing AR expression, and inducing prostatic epithelial regression. [7][8][9][10] Estrogen's actions can be mediated by estrogen receptor alpha (ERa) and ERb, 11,12 encoded by two distinct genes. Studies conducted with conventional neomycin (Neo) gene knockin and ER knockout (KO) mice suggested that ERa, but not ERb, acts as a dominant receptor of estrogen signaling in males for the development of prostate and for maintenance of normal reproductive functions.…”
Section: Introductionmentioning
confidence: 99%